Weldable high-strength ethylene propylene diene monomer waterproof roll and preparation process thereof
By using a combination of trimellitic anhydride and modified silica in the waterproof coil of ethylene propylene rubber, the problem of insufficient aging resistance in acid rain environment is solved, and the acid resistance and mechanical properties of the coil are significantly improved.
Patent Information
- Application Number
- CN202411488909.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-07
AI Technical Summary
The existing ethylene propylene rubber waterproof coils have insufficient aging resistance in harsh environments with severe acid rain, which cannot meet the needs in actual use.
Using trimellitic anhydride as an acid-resistant additive and modified silica, zeolite powder, carbon black and chopped glass fiber, the process of enhancing Ethylene and Certainty-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mercedes-Mer Acid resistance and mechanical properties of rubber waterproof coils.
It significantly improves the aging resistance and mechanical properties of EPDM rubber waterproof coil under acidic conditions, ensuring its stability and acid resistance in the environment invading acid rain.
Smart Images

Figure CN119264569A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of EPDM rubber, and in particular to a weldable high-strength EPDM rubber waterproof coiled material and a preparation process thereof. Background Art
[0002] There are many types of waterproofing membranes, mainly including five types: coating waterproofing materials, polymer waterproofing membranes, modified asphalt waterproofing membranes, rigid water-stopping materials and sealing materials. Among them, polymer waterproofing membranes occupy an important position in the field of high-end waterproofing membranes due to their advantages such as good durability and convenient construction. Polymer waterproofing membranes are mainly divided into two categories: synthetic resins and synthetic rubbers. In recent years, ethylene propylene diene monomer rubber (EPDM) waterproofing membranes have made continuous breakthroughs in construction technology and material technology. Compared with traditional waterproofing membranes, they have better tear resistance, fatigue resistance and corrosion resistance. Using them in building waterproofing projects can greatly improve the waterproofing quality and durability, and therefore have received widespread attention.
[0003] For example, Chinese patent CN113789014B discloses a weldable EPDM waterproofing membrane, which comprises the following components: EPDM rubber; high-density polyethylene; dibasic acid pine oil monoester; compatibilizer; reinforcing filler; anti-aging agent; vulcanizer; vulcanization activator. The preparation method comprises the following steps: S1, weighing EPDM rubber, high-density polyethylene, dibasic acid pine oil monoester, compatibilizer, anti-aging agent, reinforcing filler, mixing evenly and vulcanizing to obtain a mixture; S2, shaping to obtain a molded part; S3, trimming and rolling to obtain a finished waterproofing membrane.
[0004] Although the above patent improves the mechanical properties of waterproof membranes to a certain extent, when the waterproof membranes are laid for a long time in harsh outdoor environments, especially in areas where acid rain is becoming increasingly serious, the aging resistance of the above patent cannot meet the needs of actual application.
[0005] Based on this, the present invention designs a weldable high-strength EPDM rubber waterproofing membrane and a preparation process thereof to solve the above problems. Summary of the invention
[0006] In view of the above-mentioned shortcomings of the prior art, the present invention provides a weldable high-strength EPDM rubber waterproofing membrane and a preparation process thereof.
[0007] To achieve the above purpose, the present invention is implemented by the following technical scheme: a weldable high-strength EPDM rubber waterproofing coiled material, comprising the following raw materials: 100-105 parts of EPDM rubber, 6.4-7.8 parts of acid-resistant additive, 1.2-1.5 parts of sulfur, 0.7-1.6 parts of stearic acid, 2.6-3.2 parts of accelerator, 32-45 parts of reinforcing filler, 3.4-5.8 parts of antioxidant; The acid-resistant auxiliary agent comprises the following raw materials: trimellitic anhydride, modified silicon dioxide and ethanol.
[0008] Furthermore, the reinforcing filler is a mixture of zeolite powder, carbon black and chopped glass fibers in a mass ratio of 12-16:15-21:28-35.
[0009] Furthermore, the antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 25-31:18-22.
[0010] Furthermore, the accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.5-1.7:1.9-2.6:1.7-2.4.
[0011] A preparation process of the weldable high-strength EPDM rubber waterproofing coiled material comprises the following steps: Step 1: preparing modified silica; Soak the preheated silica in the pickling solution until it is submerged, and pickle at 42-47°C for 1-2 hours to remove trace metals in the silica; The acid-washed and impurity-removed silica is dried, and then silane coupling agent KH-560 is added, and the excess silane coupling agent KH-560 is removed by stirring and filtering to obtain modified silica; Step 2: preparing acid-resistant additive; Dissolve trimellitic anhydride in an ethanol solution, add modified silica, stir for 35-45 minutes, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; Step 3: Add zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 80-85°C, add 1 / 4-1 / 3 of an acid-resistant additive, heat and mix evenly; continue to add 1 / 4-1 / 3 of the acid-resistant additive, heat and mix evenly; add the remaining acid-resistant additive, heat and mix evenly to obtain an acid-resistant filler; Step 4: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, kneading, extruding, coating with welding strips, vulcanizing, cooling, and winding the mixture A to obtain a weldable high-strength EPDM rubber waterproof membrane.
[0012] Furthermore, the pickling step in step 1 is specifically as follows: the silicon dioxide preheated to 40-45° C. is immersed in a pickling solution with a pH of 1.2-1.4 until it is submerged, and pickled at 42-47° C. for 1-2 hours to remove trace metals in the silicon dioxide.
[0013] Furthermore, the modification step in step 1 is specifically as follows: drying the acid-washed and impurity-removed silica, adding silane coupling agent KH-560, stirring at 200-300 r / min for 20-40 min, filtering to remove excess silane coupling agent KH-560, and obtaining modified silica.
[0014] Furthermore, step 2 is specifically as follows: dissolving 14-18 parts of trimellitic anhydride in 45-57 parts of ethanol solution, adding modified silica, stirring at 200-300 r / min for 35-45 min, and recovering ethanol by vacuum distillation to obtain an acid-resistant additive; Furthermore, the mass ratio of trimellitic anhydride to modified silica is 14-18:8-12.
[0015] Furthermore, step three is specifically as follows: zeolite powder, carbon black N330 and chopped glass fiber are put into a ball mill and mixed evenly to obtain a reinforcing filler, the reinforcing filler is heated to 80-85°C, 1 / 4-1 / 3 of an acid-resistant additive is added, the temperature is increased by 2-3°C, and the mixture is mixed at 200-300r / min for 15-20min; 1 / 4-1 / 3 of an acid-resistant additive is continued to be added, the temperature is increased by 2-3°C, and the mixture is mixed at 200-300r / min for 20-25min; the remaining acid-resistant additive is added, the temperature is increased to 98-100°C, and the mixture is mixed at 200-300r / min for 25-30min to obtain an acid-resistant filler.
[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. After a certain amount of trimellitic anhydride is added to the present invention, although it will have a certain impact on the elongation at break of the material, due to its characteristics as an acid derivative, it shows stability that is difficult to react with acid. More importantly, the compounding of trimellitic anhydride and short glass fibers significantly enhances the effect of the EPDM rubber waterproofing membrane maintaining its excellent aging resistance under acidic conditions, ensuring that the mechanical properties of the EPDM rubber waterproofing membrane remain stable even in the harsh environment of acid rain.
[0017] 2. The present invention integrates the acid-resistant additive into the reinforcing filler in batches, which effectively promotes the close combination between the two and subtly improves the ability of the EPDM rubber waterproof membrane to resist acid rain erosion; it is particularly noteworthy that as the immersion time of the material in the acidic solution increases, the effect of improving its acid resistance becomes more and more significant.
[0018] 3. The present invention successfully optimizes the tear strength and tensile strength of the EPDM rubber waterproofing membrane by modifying the silicon dioxide, making its mechanical properties more excellent. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] The drawings constituting a part of the present application are used to provide a further understanding of the invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 The graphs showing the change in tensile strength of each group of products after being immersed in a sulfuric acid and nitric acid mixture are shown; Figure 2 The tear strength variation curves of each group of products after being immersed in a sulfuric acid and nitric acid mixture are shown; Figure 3 The graph shows the elongation at break variation curves of each group of products after being immersed in a mixture of sulfuric acid and nitric acid. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0021] This embodiment provides a preparation process of a weldable high-strength EPDM rubber waterproofing membrane, comprising the following steps: Step 1: Weigh the raw materials: 105kg EPDM rubber, 1.5kg sulfur, 1.6kg stearic acid, 3.2kg accelerator, 45kg reinforcing filler, 5.8kg antioxidant; The reinforcing filler is a mixture of zeolite powder, carbon black N330 and chopped glass fibers in a mass ratio of 16:21:35; The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 31:22; The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.7:2.6:2.4; Step 2: preparing modified silica; The silica preheated to 45°C was immersed in a pickling solution with a pH of 1.4 until it was submerged, and pickled at 47°C for 2 hours to remove trace metals in the silica; The acid-washed and impurity-removed silica was dried, and then silane coupling agent KH-560 was added, and the mixture was stirred at 300 r / min for 40 min, and the excess silane coupling agent KH-560 was removed by filtration to obtain modified silica; The mass ratio of the silicon dioxide to the silane coupling agent KH-560 is 1:1.5; The particle size of the silicon dioxide is 10 microns; Step 3: preparing acid-resistant additive; Dissolve 18 kg of trimellitic anhydride in 57 kg of 70% ethanol solution, add modified silica, stir at 300 r / min for 45 min, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; The mass ratio of trimellitic anhydride to modified silicon dioxide is 18:12; Weigh 7.8 kg of acid-resistant additive; Step 4: Put zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 85°C, add 1 / 3 of the acid-resistant additive, increase the temperature by 3°C, and mix at 300r / min for 20min; continue to add 1 / 3 of the acid-resistant additive, increase the temperature by 3°C, and mix at 300r / min for 25min; add the remaining acid-resistant additive, increase the temperature to 100°C, and mix at 300r / min for 30min to obtain an acid-resistant filler; Step 5: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, and putting the mixture A into an open mill, controlling the mixing temperature at 140° C., and the mixing time for 12 min; Step 6: Extrusion molding through a cold feed extruder, the barrel temperature of the cold feed extruder is controlled at 45°C; Step 7: Hot melt the extruded product, fix it at 5 cm from the edge, and put it into the vulcanizer with the conveyor cloth for vulcanization. The vulcanization temperature of the vulcanizer is 160°C, the vulcanization pressure is 0.3 MPa, and the vulcanization time is 10 minutes. Step 8: The vulcanized product is cooled by cooling water and then rolled to obtain a weldable high-strength EPDM rubber waterproofing membrane.
[0022] The mixing process uses an XL-KLYP1 two-roller mill from Dongguan Xilong Electrical Machinery Equipment Co., Ltd.; the vulcanization process uses a TDC-250T-V-4RT vacuum rubber plate vulcanizer purchased from Haimen Dongda Machinery Technology Co., Ltd. Example
[0023] This embodiment provides a preparation process of a weldable high-strength EPDM rubber waterproofing membrane, comprising the following steps: Step 1: Weigh the raw materials: 100kg EPDM rubber, 1.2kg sulfur, 0.7kg stearic acid, 2.6kg accelerator, 32kg reinforcing filler, 3.4kg antioxidant; The reinforcing filler is a mixture of zeolite powder, carbon black N330 and chopped glass fibers in a mass ratio of 12:15:28; The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 25:18; The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.5:1.9:1.7; Step 2: preparing modified silica; The silica preheated to 40°C was immersed in a pickling solution with a pH of 1.2 until it was submerged, and pickled at 42°C for 1 hour to remove trace metals in the silica; The acid-washed and impurity-removed silica was dried, and then silane coupling agent KH-560 was added, and the mixture was stirred at 200 r / min for 20 min, and the excess silane coupling agent KH-560 was removed by filtration to obtain modified silica; The mass ratio of the silicon dioxide to the silane coupling agent KH-560 is 1:1.2; The particle size of the silicon dioxide is 5 microns; Step 3: preparing acid-resistant additive; Dissolve 14 kg of trimellitic anhydride in 45 kg of 70% ethanol solution, add modified silica, stir at 200 r / min for 35 min, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; The mass ratio of trimellitic anhydride to modified silicon dioxide is 14:8; Weigh 6.4 kg of acid-resistant additive; Step 4: Put zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 80°C, add 1 / 4 of the acid-resistant additive, increase the temperature by 2°C, and mix at 200r / min for 15min; continue to add 1 / 4 of the acid-resistant additive, increase the temperature by 2°C, and mix at 200r / min for 20min; add the remaining acid-resistant additive, increase the temperature to 98°C, and mix at 200r / min for 25min to obtain an acid-resistant filler; Step 5: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, and putting the mixture A into an open mill, controlling the mixing temperature at 140° C., and the mixing time for 12 min; Step 6: Extrusion molding through a cold feed extruder, the barrel temperature of the cold feed extruder is controlled at 45°C; Step 7: Hot melt the extruded product, fix it at 5 cm from the edge, and put it into the vulcanizer with the conveyor cloth for vulcanization. The vulcanization temperature of the vulcanizer is 160°C, the vulcanization pressure is 0.3 MPa, and the vulcanization time is 10 minutes. Step 8: The vulcanized product is cooled by cooling water and then rolled to obtain a weldable high-strength EPDM rubber waterproofing membrane. Example
[0024] This embodiment provides a preparation process of a weldable high-strength EPDM rubber waterproofing membrane, comprising the following steps: Step 1: Weigh the raw materials: 102kg EPDM rubber, 1.3kg sulfur, 1.1kg stearic acid, 2.9kg accelerator, 41kg reinforcing filler, 4.2kg antioxidant; The reinforcing filler is a mixture of zeolite powder, carbon black N330 and chopped glass fibers in a mass ratio of 15:20:32; The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 30:21; The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.6:2.1:2.1; Step 2: preparing modified silica; The silica preheated to 42°C was immersed in a pickling solution with a pH of 1.2 until it was submerged, and pickled at 45°C for 2 hours to remove trace metals in the silica; The acid-washed and impurity-removed silica was dried, and then silane coupling agent KH-560 was added, and the mixture was stirred at 280 r / min for 30 min, and the excess silane coupling agent KH-560 was removed by filtration to obtain modified silica; The mass ratio of the silicon dioxide to the silane coupling agent KH-560 is 1:1.4; The particle size of the silicon dioxide is 5 microns; Step 3: preparing acid-resistant additive; Dissolve 15 kg of trimellitic anhydride in 50 kg of 70% ethanol solution, add modified silica, stir at 280 r / min for 42 min, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; The mass ratio of trimellitic anhydride to modified silicon dioxide is 15:11; Weigh 7.6 kg of acid-resistant additive; Step 4: Add zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 82°C, add 1 / 4 of the acid-resistant additive, increase the temperature by 2°C, and mix at 280r / min for 18min; continue to add 1 / 3 of the acid-resistant additive, increase the temperature by 3°C, and mix at 280r / min for 22min; add the remaining acid-resistant additive, increase the temperature to 100°C, and mix at 280r / min for 26min to obtain an acid-resistant filler; Step 5: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, and putting the mixture A into an open mill, controlling the mixing temperature at 140° C., and the mixing time for 12 min; Step 6: Extrusion molding through a cold feed extruder, the barrel temperature of the cold feed extruder is controlled at 45°C; Step 7: Hot melt the extruded product, fix it at 5 cm from the edge, and put it into the vulcanizer with the conveyor cloth for vulcanization. The vulcanization temperature of the vulcanizer is 160°C, the vulcanization pressure is 0.3 MPa, and the vulcanization time is 10 minutes. Step 8: The vulcanized product is cooled by cooling water and then rolled to obtain a weldable high-strength EPDM rubber waterproofing membrane.
[0025] Comparative Example 1 The difference between this comparative example and Example 3 is that in step 3, the acid-resistant additive is added to the reinforcing filler at one time, rather than in batches; This comparative example provides a preparation process of a weldable high-strength EPDM rubber waterproofing membrane, comprising the following steps: Step 1: Weigh the raw materials: 102kg EPDM rubber, 1.3kg sulfur, 1.1kg stearic acid, 2.9kg accelerator, 41kg reinforcing filler, 4.2kg antioxidant; The reinforcing filler is a mixture of zeolite powder, carbon black N330 and chopped glass fibers in a mass ratio of 15:20:32; The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 30:21; The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.6:2.1:2.1; Step 2: preparing modified silica; The silica preheated to 42°C was immersed in a pickling solution with a pH of 1.2 until it was submerged, and pickled at 45°C for 2 hours to remove trace metals in the silica; The acid-washed and impurity-removed silica was dried, and then silane coupling agent KH-560 was added, and the mixture was stirred at 280 r / min for 30 min, and the excess silane coupling agent KH-560 was removed by filtration to obtain modified silica; The mass ratio of the silicon dioxide to the silane coupling agent KH-560 is 1:1.4; The particle size of the silicon dioxide is 5 microns; Step 3: preparing acid-resistant additive; Dissolve 15 kg of trimellitic anhydride in 50 kg of 70% ethanol solution, add modified silica, stir at 280 r / min for 42 min, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; The mass ratio of trimellitic anhydride to modified silicon dioxide is 15:11; Weigh 7.6 kg of acid-resistant additive; Step 4: Put zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 82°C, add an acid-resistant additive, increase the temperature by 2°C, and mix at 280r / min for 18min; continue to increase the temperature by 3°C, and mix at 280r / min for 22min; increase the temperature to 100°C, and mix at 280r / min for 26min to obtain an acid-resistant filler; Step 5: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, and putting the mixture A into an open mill, controlling the mixing temperature at 140° C., and the mixing time for 12 min; Step 6: Extrusion molding through a cold feed extruder, the barrel temperature of the cold feed extruder is controlled at 45°C; Step 7: Hot melt the extruded product, fix it at 5 cm from the edge, and put it into the vulcanizer with the conveyor cloth for vulcanization. The vulcanization temperature of the vulcanizer is 160°C, the vulcanization pressure is 0.3 MPa, and the vulcanization time is 10 minutes. Step 8: The vulcanized product is cooled by cooling water and then rolled to obtain a weldable high-strength EPDM rubber waterproofing membrane.
[0026] Comparative Example 2 The difference between this comparative example and Example 3 is that the silicon dioxide is not modified; This comparative example provides a preparation process of a weldable high-strength EPDM rubber waterproofing membrane, comprising the following steps: Step 1: Weigh the raw materials: 102kg EPDM rubber, 1.3kg sulfur, 1.1kg stearic acid, 2.9kg accelerator, 41kg reinforcing filler, 4.2kg antioxidant; The reinforcing filler is a mixture of zeolite powder, carbon black N330 and chopped glass fibers in a mass ratio of 15:20:32; The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 30:21; The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.6:2.1:2.1; Step 2: preparing acid-resistant additive; Dissolve 15 kg of trimellitic anhydride in 50 kg of 70% ethanol solution, add silicon dioxide with a particle size of 5 microns, stir at 280 r / min for 42 minutes, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; The mass ratio of trimellitic anhydride to silicon dioxide is 15:11; Weigh 7.6 kg of acid-resistant additive; Step 3: Add zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 82°C, add 1 / 4 of the acid-resistant additive, increase the temperature by 2°C, and mix at 280r / min for 18min; continue to add 1 / 3 of the acid-resistant additive, increase the temperature by 3°C, and mix at 280r / min for 22min; add the remaining acid-resistant additive, increase the temperature to 100°C, and mix at 280r / min for 26min to obtain an acid-resistant filler; Step 4: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, and putting the mixture A into an open mill, controlling the mixing temperature at 140° C. and the mixing time for 12 min; Step 5: Extrusion molding through a cold feed extruder, the barrel temperature of the cold feed extruder is controlled at 45°C; Step 6: Hot melt the extruded product, fix it at 5 cm from the edge, and put it into the vulcanizer with the conveyor cloth for vulcanization. The vulcanization temperature of the vulcanizer is 160°C, the vulcanization pressure is 0.3 MPa, and the vulcanization time is 10 minutes. Step 7: The vulcanized product is cooled by cooling water and then rolled to obtain a weldable high-strength EPDM rubber waterproofing membrane.
[0027] Comparative Example 3 The difference between this comparative example and Example 3 is that trimellitic anhydride is not added; This comparative example provides a preparation process of a weldable high-strength EPDM rubber waterproofing membrane, comprising the following steps: Step 1: Weigh the raw materials: 102kg EPDM rubber, 1.3kg sulfur, 1.1kg stearic acid, 2.9kg accelerator, 41kg reinforcing filler, 4.2kg antioxidant; The reinforcing filler is a mixture of zeolite powder, carbon black N330 and chopped glass fibers in a mass ratio of 15:20:32; The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 30:21; The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.6:2.1:2.1; Step 2: preparing modified silica; The silica preheated to 42°C was immersed in a pickling solution with a pH of 1.2 until it was submerged, and pickled at 45°C for 2 hours to remove trace metals in the silica; The acid-washed and impurity-removed silica was dried, and then silane coupling agent KH-560 was added, and the mixture was stirred at 280 r / min for 30 min, and the excess silane coupling agent KH-560 was removed by filtration to obtain modified silica; The mass ratio of the silicon dioxide to the silane coupling agent KH-560 is 1:1.4; The particle size of the silicon dioxide is 5 microns; Step 3: preparing acid-resistant additive; Add modified silicon dioxide to 50 kg of 70% ethanol solution, stir at 280 r / min for 42 min, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; The mass ratio of the ethanol solution to the modified silicon dioxide is 50:11; Weigh 7.6 kg of acid-resistant additive; Step 4: Add zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 82°C, add 1 / 4 of the acid-resistant additive, increase the temperature by 2°C, and mix at 280r / min for 18min; continue to add 1 / 3 of the acid-resistant additive, increase the temperature by 3°C, and mix at 280r / min for 22min; add the remaining acid-resistant additive, increase the temperature to 100°C, and mix at 280r / min for 26min to obtain an acid-resistant filler; Step 5: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, and putting the mixture A into an open mill, controlling the mixing temperature at 140° C., and the mixing time for 12 min; Step 6: Extrusion molding through a cold feed extruder, the barrel temperature of the cold feed extruder is controlled at 45°C; Step 7: Hot melt the extruded product, fix it at 5 cm from the edge, and put it into the vulcanizer with the conveyor cloth for vulcanization. The vulcanization temperature of the vulcanizer is 160°C, the vulcanization pressure is 0.3 MPa, and the vulcanization time is 10 minutes. Step 8: The vulcanized product is cooled by cooling water and then rolled to obtain a weldable high-strength EPDM rubber waterproofing membrane.
[0028] Experimental example 1. The mechanical properties of the products obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were tested at room temperature and pressure: The tear strength test was carried out in accordance with the standard of GB / T 12829-2006 Determination of tear strength of small specimens of vulcanized rubber or thermoplastic rubber (Delft specimen) and the result was taken as the average of the transverse and longitudinal directions; The tensile strength and elongation at break at 23°C were measured in accordance with HG T 3868-2008 Standard for Determination of High-Temperature Tensile Strength and Elongation at Break of Vulcanized Rubber, and the results were taken as the average of the transverse and longitudinal directions; the results are shown in the table below.
[0029]
[0030] 2. Test the mechanical properties of each group of products in acidic environment: The products obtained in Examples 1 to 3 and Comparative Examples 1 to 3 were immersed in a sulfuric acid and nitric acid mixture with a pH of 1 at 40°C for 0 h (T0), 30 h (T1), 60 h (T2), 90 h (T3), and 120 h (T4), respectively, and then aged in hot air at 90°C for 120 h. The mechanical properties data were then tested in the above manner. The results are shown in the attached specification. Figure 1 - Figure 3 .
[0031] According to the table above and the instructions Figure 1 - Figure 3 From the data analysis, it can be seen that although the elongation at break will be affected to a certain extent after the addition of trimellitic anhydride, the compounding of trimellitic anhydride and short-cut glass fiber has significantly improved the aging resistance of EPDM rubber waterproof membrane under acidic conditions; By adding acid-resistant additives to the reinforcing filler in batches, the combination of the two can be promoted, thereby improving the acid resistance of the EPDM rubber waterproofing membrane. The longer the immersion time in the acid solution, the more obvious the effect; the tear strength and tensile strength of the EPDM rubber waterproofing membrane are improved by modifying the silica; Trimellitic anhydride is an acid derivative, which is difficult to react with acid and is stable under acidic conditions. At the same time, the compounding of trimellitic anhydride and chopped glass fiber improves the aging resistance under acidic conditions.
[0032] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A weldable high-strength EPDM rubber waterproofing membrane, characterized in that: Including the following ingredients: 100-105 parts of EPDM rubber, 6.4-7.8 parts of acid-resistant additive, 1.2-1.5 parts of sulfur, 0.7-1.6 parts of stearic acid, 2.6-3.2 parts of accelerator, 32-45 parts of reinforcing filler, 3.4-5.8 parts of antioxidant; The acid-resistant auxiliary agent comprises the following raw materials: trimellitic anhydride, modified silicon dioxide and ethanol.
2. The weldable high-strength EPDM rubber waterproofing membrane according to claim 1, characterized in that: The reinforcing filler is a mixture of zeolite powder, carbon black and chopped glass fibers in a mass ratio of 12-16:15-21:28-35.
3. The weldable high-strength EPDM rubber waterproofing membrane according to claim 2, characterized in that: The antioxidant is a mixture of antioxidant RD and antioxidant 4010NA in a mass ratio of 25-31:18-22.
4. The weldable high-strength EPDM rubber waterproofing membrane according to claim 3, characterized in that: The accelerator is a mixture of accelerator TMTD, accelerator SA and accelerator BZ in a mass ratio of 1.5-1.7:1.9-2.6:1.7-2.
4.
5. A process for preparing a weldable high-strength EPDM rubber waterproofing membrane as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: preparing modified silica; Soak the preheated silica in the pickling solution until it is submerged, and pickle at 42-47°C for 1-2 hours to remove trace metals in the silica; The acid-washed and impurity-removed silica is dried, and then silane coupling agent KH-560 is added, and the excess silane coupling agent KH-560 is removed by stirring and filtering to obtain modified silica; Step 2: preparing acid-resistant additive; Dissolve trimellitic anhydride in an ethanol solution, add modified silica, stir for 35-45 minutes, and recover ethanol by vacuum distillation to obtain an acid-resistant additive; Step 3: Add zeolite powder, carbon black N330 and chopped glass fiber into a ball mill and mix them evenly to obtain a reinforcing filler, heat the reinforcing filler to 80-85°C, add 1 / 4-1 / 3 of an acid-resistant additive, heat and mix evenly; continue to add 1 / 4-1 / 3 of the acid-resistant additive, heat and mix evenly; add the remaining acid-resistant additive, heat and mix evenly to obtain an acid-resistant filler; Step 4: adding the accelerator mixed with stearic acid to the EPDM rubber mixed with the antioxidant to obtain a mixture A, kneading, extruding, coating with welding strips, vulcanizing, cooling, and winding the mixture A to obtain a weldable high-strength EPDM rubber waterproof membrane.
6. The preparation process of the weldable high-strength EPDM rubber waterproofing coiled material according to claim 5, characterized in that: The pickling step in step 1 is specifically as follows: the silicon dioxide preheated to 40-45° C. is immersed in a pickling solution with a pH of 1.2-1.4 until it is submerged, and pickled at 42-47° C. for 1-2 hours to remove trace metals in the silicon dioxide.
7. The process for preparing the weldable high-strength EPDM rubber waterproofing membrane according to claim 6, characterized in that: Step 1 The modification step is specifically as follows: drying the acid-washed and impurity-removed silica, adding silane coupling agent KH-560, stirring at 200-300 r / min for 20-40 min, filtering to remove excess silane coupling agent KH-560, and obtaining modified silica.
8. The process for preparing the weldable high-strength EPDM rubber waterproofing membrane according to claim 7, characterized in that: The second step is specifically as follows: dissolving 14-18 parts of trimellitic anhydride in 45-57 parts of ethanol solution, adding modified silica, stirring at 200-300 r / min for 35-45 minutes, and recovering ethanol by reduced pressure distillation to obtain an acid-resistant additive.
9. The process for preparing the weldable high-strength EPDM rubber waterproofing membrane according to claim 8, characterized in that: The mass ratio of trimellitic anhydride to modified silicon dioxide is 14-18:8-12.
10. The process for preparing the weldable high-strength EPDM rubber waterproofing membrane according to claim 9, characterized in that: Step three is as follows: zeolite powder, carbon black N330 and chopped glass fibers are put into a ball mill and mixed evenly to obtain a reinforcing filler, the reinforcing filler is heated to 80-85° C., 1 / 4-1 / 3 of an acid-resistant additive is added, the temperature is increased by 2-3° C., and mixed at 200-300 r / min for 15-20 minutes; Continue to add 1 / 4-1 / 3 of the acid-resistant additive, raise the temperature by 2-3°C, and mix at 200-300r / min for 20-25min; add the remaining acid-resistant additive, raise the temperature to 98-100°C, and mix at 200-300r / min for 25-30min to obtain the acid-resistant filler.
Citation Information
Patent Citations
A weldable EPDM waterproof membrane and its preparation method
CN113789014B